Comparison between one-leg and two-leg plyometric training on vertical jump performance - Delcore, G.; Mathieu, W.; Salazar, W.; Hernandez, J. (Medicine & Science in Sports & Exercise, 1998)
Elite female volleyball players were assigned to a control group (N = 6), a one-leg plyometric training group (N = 6), and a two-leg plyometric training group (N = 5). Jump training (4 x 12 jumps) was performed three times per week for eight weeks. Both groups undergoing plyometric training improved in a variety of parameters involved with vertical jumping however, the single-leg trained group was significantly better on all measures than the two-leg group. Implication: One-leg plyometric training is better than two-leg training for increasing vertical jump factors in female volleyball players.